Hukum Poligami: Analisis Komparatif Terhadap Pemikiran Musdah Mulia Dan Muhammad Syahrur - Muqsith, Abdurrahman; Sudirman; Fadil Sj (Al-Manhaj: Journal of Indonesian Islamic Family Law, 2022)
This study focuses on the law of polygamy by comparing the thoughts of two contemporary scholars, namely Musdah Mulia and Muhammad Syahrur in punishing polygamy so that the results obtained are Musdah punishing polygamy Haram Lighairihi provided that the fair conditions given in polygamy are impossible to implement in the present because the obligation to act fairly lies in the biological realm. Meanwhile, Muhammad Syahrur argues that polygamy is lawful and in certain situations polygamy is recommended to be carried out with the consideration that polygamy justice is only limited to the social realm of society so that being fair can still be realized in the practice of polygamy. In addition, the difference between the two figures lies in the legal istinbat used, where Musdah uses the Maudu’i interpretation method, while Syahrur uses the tahlili interpretation method.